Efektivitas Fungi Mikoriza Arbuskula Indigenous Terhadap Pertumbuhan Stek Pucuk Gosale (Syzygium Malaccense (L.) Merr & L.M Perry) - Steffani Silferansti Tak; Irdika Mansur; Prijanto Pamungkas (Jurnal Silvikultur Tropika, 2018)
Gosale (Syzygium malaccense (L.) Merr. & L.M.Perry) that belongs to the Myrtaceae family is one of the leading local plant species grown in Halmahera, North Maluku. Some problems in gosale breeding such as limited seed availability, low seed production due to seasonal fruiting and the nature of seeds that can not be stored for a long period (recalcitrant), suggest an alternative new production technique through a vegetative propagation (shoot cutting). Moreover, Improved seedling quality can be attempted by AMF inoculation, in which AMF at shoot cuttings play a role in initiating the formation of adventive roots. This study was conducted for 9 months using completely randomized design (CRD) with indigenous AMF inoculation treatment. The results showed that gosale cuttings that planted with indigenous AMF inoculation were effective at all observed variables. Inoculum AMF inoculated without the addition of host plant Pueria javanica at gosale shoot cuttings suggested the best treatment. The treatment of inoculum AMF from Kusumadehe (M1) obtained the best result in the variable of plant height increase, dry weight of shoot, dry weight of root, root shoot ratio), and seedling quality index. While the treatment of Inoculum AMF from Soakonora revealed the highest result in the variable of plant diameter increase and AMF colonization.Keywords: gosale, shoot cuttings, AMF, Pueraria javanica, West Halmahera